2016
DOI: 10.1016/j.rala.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Temperament Affects Rangeland Use Patterns and Reproductive Performance of Beef Cows

Abstract: On the Ground • The American beef industry is paying more attention to cattle temperament, but studies examining relationships between temperaments and grazing behavior or animal performance on rangelands are limited. • We studied range beef cow temperaments using the behavioral syndromes framework. Cows classified into behavioral type groups on the basis of a suite of correlated behaviors showed contrasting rangeland use patterns and different reproductive efficiency. These differences resulted in temperament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…. Cows that spent more time exploring and explored a larger portion of the range (e.g., stronger activation of SEEKING) ate quicker while in confinement, had calves with heavier weaning weights, higher cortisol concentrations during confinement, and shorter postpartum intervals to estrus 29 . Therefore, the SEEKING system can have production and welfare implications.…”
mentioning
confidence: 99%
“…. Cows that spent more time exploring and explored a larger portion of the range (e.g., stronger activation of SEEKING) ate quicker while in confinement, had calves with heavier weaning weights, higher cortisol concentrations during confinement, and shorter postpartum intervals to estrus 29 . Therefore, the SEEKING system can have production and welfare implications.…”
mentioning
confidence: 99%
“…Both the animal's genetics and his or her previous experiences have an effect on behavior (Grandin, 1997;Grandin & Shively, 2015). Research with global positioning system collars has shown that some cattle are more active grazers and will walk farther than others (Goodman, Cibils, & Weley, et al, 2016). Researchers called them "go getters" and "laid-back" types of grazing patterns (Goodman et al, 2016).…”
Section: Still Resistance In Accepting Animal Emotionsmentioning
confidence: 99%
“…Research with global positioning system collars has shown that some cattle are more active grazers and will walk farther than others (Goodman, Cibils, & Weley, et al, 2016). Researchers called them "go getters" and "laid-back" types of grazing patterns (Goodman et al, 2016). It is likely that the "go getters" are high in the seek emotion.…”
Section: Still Resistance In Accepting Animal Emotionsmentioning
confidence: 99%
“…These authors reported that cows belonging to the 'go-getter' behavioral type weaned a heavier calf, achieved BW nadir after calving 25 d sooner, and had a resumption of estrus 18 d sooner than their 'laid back' counterparts. Over a 7 yr period, Goodman et al (2016) retrospectively analyzed culling rates of the two behavioral types and reported that the population of the herd at the Corona Range and Livestock Research Center shifted toward a population composed of 'go-getters' (Fig. 1).…”
Section: Behavior and Social Aspectsmentioning
confidence: 99%
“…Cumulative culling rate for range beef cows at the Corona Range and Livestock Research Center, Corona, NM classified into two behavioral types, 'go-getters' or 'laid back'. Adapted fromGoodman et al (2016).…”
mentioning
confidence: 99%